The effect of locomotor and non-locomotor movement in response to music among five and six year olds / Gan Ann Kee - Gan , Ann Kee (2018)
Movement involvement in music is a concept widely recognized by many well-known music educators such as Zoltan Kodaly, Carl Orff and Emile Jaques-Dalcroze. Teaching music with movement is especially effective for young children (Pound & Harrison, 2002). Young children develop the understanding of musical elements by involving movement (Carlson, 1980). This study was conducted to find out the difference between various movement categories in response to music among 5- and 6-year-old children. The two movement categories focused on this study were locomotor and non-locomotor movement. Sixty-one children aged five to six from a music centre and two kindergartens in the Klang Valley participated in this study, and were randomly assigned into either one of the groups, locomotor or non-locomotor. Children attended a total of six one-hour lessons, with either a locomotor or non-locomotor movement treatment. The study was conducted on a weekly basis, excluding a pre-test and post-test session, which were scheduled before and after the six weekly lessons. Data from the pre-test and post-test were analysed based on different movement categories, age and gender. Children from both groups showed improvement in movement responses to music, however, there was no significant relationship found between locomotor and non-locomotor movement, and gender and movement in response to music. Therefore, gender was not an affective variable in this study.